STORE ATMOSPHERE ON CONSUMER IMPULSIVE BUYING BEHAVIOR AT MULTI MART II SUPERMARKET MANADO - Makal, Eirene Natalia; Pangemanan, Sifrid S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Impulse buying is an important phenomenon in consumer behavior and retailing. The condition of the consumptive behavior of people in Manado might be related to the impulsive buying behavior. Store atmosphere are usually aimed at digging deeper into the consumersâ€™ purses at the point of purchase through encouraging impulsive or unplanned purchases. The purpose of this research is to analyze the influence of store atmosphere (exterior, general interior, store layout, interior display and human variable) on impulsive buying behavior both partially and simultaneously. The population observed is people who have purchased impulsively at Multi Mart II supermarket Manado with sample size as many as 100 respondents. This research used quantitative analyze by using questionnaires and used Multiple Regression Analysis. The conclusion is exterior, general interior, store layout, interior display and human variable influence impulsive buying behavior both simultaneously and partially. This study suggests to management of Multi Mart II supermarket to improve its exterior and interior display as attractive as possible to increase consumer impulsive buying behavior. Â  Keywords: impulsive buying, store atmosphere